The Contribution of Optimism to Resilience in Employees Experiencing Termination of Employment - Asha Kamangat Tanjung; Arthur Huwae (Journal of Psychology and Instruction, 2022)
The problems that arise from the COVID-19 pandemic have impacted all aspects of human life, one of which is termination of employment. Termination of employment is something that is feared by all workers. There are varied reactions given by both employees and the environment. There were employees who can be resilient and accept the situation they are in, on the other side there were employees who did not accept their situation and have difficulty facing various obstacles because of the loss of self-optimism. Therefore, this study aims to analyze the contribution of optimism to the resilience of employees who experienced termination of employment.  This research used quantitative method with a simple regression design. The participants of this study involved 40 people using incidental sampling technique.  The measurement of this research used an optimism scale and a resilience scale. Data analysis for testing the research hypothesis uses a simple regression test. The results showed that optimism had no effect on the resilience of employees who experienced termination of employment with a t value of 1.320 < t table of 1.685. This indicates that optimism is not a factor that triggers individuals to be resilient from bad situations due to experiencing layoffs.